Two new combinations and a key to the species of the genus Earota Mulsant & Rey (Coleoptera: Staphylinidae: Aleocharinae) - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2014)
Earota babai (Sawada, 1989), comb. nov. and Earota koreana (Paśnik, 2001), comb. nov. are transferred from the genera Pelioptera Kraatz, 1857 and Aloconota Thomson, 1858, respectively. Earota babai is recorded from the Korean Peninsula for the first time and E. koreana is a new addition to South Korea. Redescriptions, habitus photographs, illustrations of diagnostic characters of these two species and a key to the known species of the genus Earota Mulsant & Rey, 1874 are provided to facilitate identification.